A Systematic Review of Vocabulary Journals in EFL Learning: Theory, Practice, and Language Development - Erniwati; Sudarkam R. Mertosono; Muhammad Arid (FOSTER: Journal of English Language Teaching, 2026)
Vocabulary knowledge is fundamental to second and foreign language acquisition. However, developing both vocabulary breadth and depth remains a challenge in an English as a Foreign Language (EFL) context. This study examines how vocabulary is conceptualized and taught, explores the theoretical and pedagogical foundations of vocabulary journals, and evaluates their impact on learners’ vocabulary acquisition and language development. Using a systematic literature review guided by PRISMA principles, this study synthesizes findings from selected empirical and theoretical studies. The data were analyzed thematically to identify recurring patterns, theoretical alignments, and pedagogical implications. The findings indicate that vocabulary is a multidimensional construct involving both breadth and depth of knowledge. Vocabulary journals are grounded in key theoretical frameworks, including cognitive processing theories, the involvement load hypothesis, the noticing hypothesis, dual coding theory, and self-regulated learning. The results show that vocabulary journals enhance vocabulary acquisition by promoting deeper cognitive engagement, repeated exposure, and learner autonomy. They also contribute to the development of reading, writing, speaking, and listening skills. However, variations in journal design and implementation lead to inconsistencies in outcomes, which can affect the overall effectiveness of vocabulary journals in enhancing language skills. This study emphasizes the necessity of effective design and integration of vocabulary journals and calls for further research on their long-term impact.